PERBANDINGAN HASIL BELAJAR BAHASA INDONESIA DALAM PEMBELAJARAN YANG MEMILIKI KEMAMPUAN AWAL TINGGI DAN RENDAH SISWA KELAS X SMA NEGERI 1 ANGKOLA BARAT - Hasian Romadon Tanjung (Jurnal Education and Development, 2018)
Hasian Romadon Tanjung Dosen Tetap Yayasan di STKIP Tapanuli Selatan Abstract Students’ achievement in Bahasa Indonesia at the X grade students in this school doesnot get the standard minimum score. It shows that there is a problem which faced by students and teacher in learning process. This research uses experiment method. Experiment class I (X1) and experiment class II (X3). The location of the research is SMA Negeri 1 Sitinjak. The population of the research is all X grade students of SMA Negeri 1 Sitinjak that consist of four classes. The sampling technique is purposive sampling. Based on the development of the instrument in this research, so it is used: (1) instrument arrangement, (2) instrument validity. After normaility testing and final variant test of homogenity , then hypothesis testing. Students who have high achievement in XI class X1 N=10, x=27,1, S=1,95. Then students who study in X3, N=10, x=23,1, S=2,33. The criteria of Ho testing is accepted if -tt < th < tt with dk= n1 + n2 – 2 dan opportunity (1-½a). For the other t, Ho is rejected. Based on t testing at 0.05% level, it is got th = 4228 >, tt = 1,73 (H1 is accepted). After normality and final variant test of homogenity are done, then the hypothesis testing. Students who have low achievement study in X1 class where N=10, x=21,3, S=3,46. Siswa kelas X3, N=10, x=18,8, S=2,65. The criteria of Ho is accepted if -tt < th < tt with dk= n1 + n2 – 2 and opportunity (1-½a). For the other t, Ho is rejected. Based on the t testing at the 0.05% level, it is got th = 1,851> tt = 1,73 (H1 is accepted).